2018
DOI: 10.1128/msystems.00112-18
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Aspergillus niger Isolated from the International Space Station

Abstract: A thorough understanding of how fungi respond and adapt to the various stimuli encountered during spaceflight presents many economic benefits and is imperative for the health of crew. As A. niger is a predominant ISS isolate frequently detected in built environments, studies of A. niger strains inhabiting closed systems may reveal information fundamental to the success of long-duration space missions. This investigation provides valuable insights into the adaptive mechanisms of fungi in extreme environments as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 73 publications
(96 reference statements)
8
49
0
Order By: Relevance
“…condensate) could support biofouling, biofilm formation and material damage through acid production (6,7375). This is particularly important with respect to fungal growth, as these might affect human health indirectly by causing allergic reactions and asthmatic responses (17,7678).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…condensate) could support biofouling, biofilm formation and material damage through acid production (6,7375). This is particularly important with respect to fungal growth, as these might affect human health indirectly by causing allergic reactions and asthmatic responses (17,7678).…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications focused on the microbial analysis of ISS debris and dust (12–15), the study of the astronauts’ microbiome (16), the characterization of bacterial and fungal isolates from the ISS (17,18) and the (molecular) microbial analysis of swab and wipe samples taken inside the ISS (19). A study investigating the growth behavior of non-pathogenic (terrestrial) bacteria aboard the ISS found no changes in most bacteria, given that they have enough nutrients (11).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the sterilization of food and equipment prior to launch, the harsh conditions of space travel, and the isolation from any outside microbial source, contributes to the development of a low-diversity microbial community which is both sparse and tough [28,216,217], and does not make for pleasant company [218][219][220]. The harsh conditions and increase in radiation can contribute to accelerated evolution; a distinct strain of Aspergillus niger was isolated from the International Space Station [221]. Over time, rapid evolution to support hardiness can lead to the development of 'survivor strains' which are extremely difficult to kill or eradicate, and recent research has demonstrated this in the built environment [222].…”
Section: The Lifelong Impact Of Microbial Roommatesmentioning
confidence: 99%
“…Characterization of different Aspergillus strains isolated from the ISS, e.g. A. fumigatus (Knox et al 2016) and A. niger (Romsdahl et al 2018b), revealed significant spaceflight-induced changes. For instance, more pigmentation, increased growth rate and differences in proteome profiles (mainly stress resistance and nutrient acquisition) were observed, when compared with the Earth-type strains.…”
Section: Fungi In the Space Environmentmentioning
confidence: 99%
“…For instance, more pigmentation, increased growth rate and differences in proteome profiles (mainly stress resistance and nutrient acquisition) were observed, when compared with the Earth-type strains. Characterization of A. niger showed an overall increased secondary metabolite production (Romsdahl et al 2018b). Draft genome sequences of fungal strains exposed to microgravity at the ISS, among them A. niger, were made available and have been published (Singh et al 2017).…”
Section: Fungi In the Space Environmentmentioning
confidence: 99%